Modelling the temperature rise effect through high-pressure torsion. Issue 12 (12th August 2016) - Parvin, H.; Kazeminezhad, M.
Abstract : An approach composed of the thermodynamics-based dislocation model and the Taylor theory is used to investigate the evolution of microstructure and flow stress during high-pressure torsion (HPT). The incremental temperature rise is considered through the modelling of HPT. The temperature can affect the annihilation of dislocations and thus the dislocation density. The model predicts the dislocation density, sub-grain size and flow stress during HPT. The modelling results are compared with the experimental data and the modelling results without considering the incremental temperature rise. A remarkable agreement is observed between the modelling results with considering the temperature rise effect and the experimental data.